Hubungan Jumlah Lekosit dengan Derajat Keparahan Pasien Stroke Iskemik Berdasarkan National Institute Of Health Stroke Scale - TSALIS YUNA HAFSHOH; Olivia Mahardani Adam; SIHNING EJT (HANG TUAH MEDICAL JOURNAL, 2020)
Abstract Background: Stroke is one of ten diseases that cause death in the world. Based on the WHO report there were 6.7 million deaths because strokes from the total deaths caused by non-communicable diseases. Based on the pathophysiology of acute ischemic stroke, leukocytes play an important role in the deterioration and clinical manifestations of patients by releasing inflammatory mediators, plugging mechanism in microcirculation, and vasoconstriction. Method: This study was using cross-sectional design. The sampling technique was purposive sampling with a total sample of 34 ischemic stroke patients. Collecting data leukocyte count using laboratory examination and scoring of severity ischemic stroke patient by using National Institute Of Health Stroke Scale (NIHSS) score. Result : the study showed 24 (70.6%) ischemic stroke patients with normal leukocyte counts, and 10 (29.4%) ischemic stroke patients with leukocytosis. 18 (52.9%) patients had mild ischemic stroke severity, 10 (29.4%) patients had moderate ischemic stroke severity, 6 (17.6%) patients had severe ischemic stroke severity. Results of the statistical analysis showed that there was a significant correlation between leukocyte count with severity of stroke based on the NIHSS score p = 0.006 <α (0.05). Conclusion : There was a significant correlation between leukocyte count with severity of stroke based on the NIHSS score.